(untitled) (Vietnam Journal of Community Medicine, 2025)
Research objective: To describe the current state of depression, anxiety, stress and psychological support needs of colorectal cancer patients treated at Nghe An Oncology Hospital. Research method: Cross-sectional description of 178 colorectal cancer patients diagnosed by histopathology from October 2023 to May 2024. Research results: Average age 60 ± 12.15 (Lowest: 19; Highest: 90 years old); Males accounted for 57.9%; the majority were farmers: 39.3%. Disease characteristics: Stage III has the highest rate of 53.9%, no metastasis 60.1%; chemotherapy alone was 51.7%; The time of disease detection > 12 months accounted for the highest rate of 34.8% and side effects after treatment accounted for 93.3%. The overall rate of depression was 74.7%, anxiety 69.7% and stress 52.8%. 100% of colorectal cancer patients had a need for psychosocial support, of which the need for high support was 24.2%. Conclusion: The rate of depression, anxiety, and stress in colorectal cancer patients was quite high. Most patients had a need for psychosocial support. Early psychological interventions with appropriate solutions are needed to help patients increase treatment effectiveness and improve their quality of life.